Copper-cerium-based core-shell catalyst and preparation method thereof

By using the preparation method of copper cerium-based core-shell catalyst, Cu-O-Ce structure is formed and Mn doped, the problem of poor stability of Mn-doped copper-based catalyst in the prior art is solved, and the elemental mercury and escape ammonia are achieved. Excellent synergistic oxidation performance.

CN119386879APending Publication Date: 2025-02-07NORTH CHINA ELECTRIC POWER UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411398598.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing Mn-doped copper-based catalysts have poor stability in the catalyst, resulting in poor synergistic oxidation effect of elemental mercury and escape ammonia.

Method used

The Cu-O-Ce structure is formed by using the preparation method of a copper cerium-based core-shell catalyst by magnetic stirring and heating and doping in the vacuum reaction chamber, and the stability and activity of the catalyst are improved by doping Mn.

Benefits of technology

The coordinated oxidation performance of the catalyst to elemental mercury and escape ammonia is significantly improved, and the SO2 tolerance and stability of the catalyst are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119386879A_ABST
    Figure CN119386879A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a copper-cerium-based core-shell catalyst, which comprises the following steps: A, putting Cu (NO3) 2.3 H2O into an ethanol aqueous solution, then adding TiO2, a NaOH aqueous solution and a glucose aqueous solution, and uniformly mixing and precipitating the solutions through magnetic stirring; b, the solution is subjected to suction filtration and vacuum drying, and a Cu2O-TiO2 sample is obtained; c, carrying out Mn doping treatment on the Cu2O-TiO2 sample; d, carrying out annealing treatment on the Cu2O-TiO2 sample subjected to the doping treatment; e, the annealed Cu2O-TiO2 sample is added into an ethanol water solution, then a NaCl water solution and a (NH4) 2Ce (NO3) 6 ethanol solution are sequentially added, and uniform mixing and precipitation of the solutions are achieved through magnetic stirring; and F, centrifugally separating and drying the solution obtained in the step E, and finally calcining the dried product to obtain the copper-cerium-based core-shell catalyst. According to the invention, the defects in the prior art can be overcome, and the synergistic oxidation effect of the catalyst on elemental mercury and escape ammonia is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalyst preparation, in particular to a copper-cerium-based core-shell catalyst and a preparation method thereof. Background Art

[0002] Coal-fired power plants provide a strong guarantee for social development, but they also aggravate environmental pollution due to the emission of coal-fired flue gas. Among them, the escaped ammonia and mercury in the flue gas during the process of ammonia selective catalytic reduction denitrification (NH3-SCR) have attracted wide attention from countries around the world. Therefore, a suitable catalyst is used to remove NH3 and Hg at the tail of SCR. 0 Simultaneous removal has become an important research direction.

[0003] The copper-based catalyst has both ammonia oxidation and mercury oxidation activity, and Ce in CeO2 4+ With Ce 3+ The valence conversion between them will produce abundant oxygen vacancies in the catalyst, which makes it have good oxygen storage capacity and oxygen release activity, and has an important influence on the adsorption and catalytic activity of the catalyst. CuO and CeO2 will form a Cu-O-Ce structure at the core-shell interface, and their interaction is conducive to improving the oxidation activity of the catalyst, thereby enhancing the catalyst's NH3 / Hg 0 In addition, by doping Mn, the combination of Cu sites with SO2 in flue gas is reduced, which can protect the active components and improve the SO2 tolerance of the catalyst.

[0004] However, the existing Mn doping is basically completed through the co-precipitation method. The Mn doped by this process has poor stability in the catalyst, resulting in poor synergistic oxidation effect of the catalyst for elemental mercury and escaped ammonia. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a copper-cerium-based core-shell catalyst and a preparation method thereof, which can solve the deficiencies of the prior art and improve the synergistic oxidation effect of the catalyst on elemental mercury and escaped ammonia.

[0006] In order to solve the above technical problems, the technical solutions adopted by the present invention are as follows.

[0007] A method for preparing a copper-cerium-based core-shell catalyst comprises the following steps:

[0008] A. Put Cu(NO3)2·3H2O into ethanol aqueous solution, perform the first magnetic stirring, transfer the ethanol aqueous solution to a water bath heating environment, perform the second magnetic stirring, then add TiO2, perform the third magnetic stirring, then add NaOH aqueous solution, perform the fourth magnetic stirring, then add glucose aqueous solution, perform the fifth magnetic stirring;

[0009] B. Filter the solution to obtain a yellow precipitate, wash the precipitate with deionized water and anhydrous ethanol respectively, and then vacuum dry to obtain a Cu2O-TiO2 sample;

[0010] C. Place the Cu2O-TiO2 sample in a vacuum reaction chamber, heat the Cu2O-TiO2 sample after evacuation, and then introduce argon gas mixed with methyl manganocene for doping treatment;

[0011] D. Annealing the Cu2O-TiO2 sample after doping;

[0012] E. Add the annealed Cu2O-TiO2 sample to an ethanol aqueous solution, then add an NaCl aqueous solution and a (NH4)2Ce(NO3)6 ethanol solution in sequence, and then perform the sixth magnetic stirring, and then transfer the mixed solution to a water bath heating environment and perform the seventh magnetic stirring;

[0013] F. The solution obtained in step E is centrifuged, the precipitate is washed with ethanol for several times, and dried under vacuum, and finally the dried product is calcined to obtain a copper-cerium-based core-shell catalyst.

[0014] Preferably, in step A, the concentration of the ethanol aqueous solution is 0.1 mmol / L, the first magnetic stirring time is 2 h, the water bath heating temperature is 60 ° C, the second magnetic stirring time is 10 min, the mass ratio of TiO2 to Cu element is 20:1, the third magnetic stirring time is 30 min, the concentration of the NaOH aqueous solution is 1 mol / L, the fourth magnetic stirring time is 30 min, the concentration of the glucose aqueous solution is 4 mol / L, the fifth magnetic stirring time is 1 h, and the volume ratio of the ethanol aqueous solution, the NaOH aqueous solution and the glucose aqueous solution is 5:5:1.

[0015] Preferably, in step B, the precipitate is washed three to four times with deionized water and anhydrous ethanol respectively, and then vacuum dried at 50° C. for 24 hours.

[0016] Preferably, in step C, the vacuum degree is drawn to less than 1×10 -3 Torr, the Cu2O-TiO2 sample was heated to 850℃, the content of methyl manganocene was 15mg / L, the flow rate of argon was 25sccm, the introduction of argon was stopped after 10min, the temperature was lowered to 600℃, maintained for 30min, then lowered to room temperature, the vacuum was broken, and the doping treatment was completed.

[0017] Preferably, in step D, the doped Cu2O-TiO2 sample is first heated to 980°C and maintained for 5 hours, then cooled to 350°C at a rate of 30°C / h and maintained for 24 hours, and then cooled to room temperature at a rate of 80°C / h to complete the annealing treatment.

[0018] Preferably, in step E, the concentration of the ethanol aqueous solution is 0.1 mmol / L, the concentration of the NaCl aqueous solution is 0.855 mol / L, the concentration of (NH4)2Ce(NO3)6 in the (NH4)2Ce(NO3)6 ethanol solution is 0.1 mmol / L, the time of the sixth magnetic stirring is 30 min, the water bath heating environment temperature is 40°C, the time of the seventh magnetic stirring is 1 h, and the volume ratio of the ethanol aqueous solution, the NaCl aqueous solution and the (NH4)2Ce(NO3)6 ethanol solution is 20:2:5.

[0019] Preferably, in step F, the calcination temperature is 400° C. and the calcination time is 1 h.

[0020] A copper-cerium-based core-shell catalyst is prepared using the above-mentioned method for preparing the copper-cerium-based core-shell catalyst.

[0021] The beneficial effect brought about by adopting the above technical solution is that the copper-cerium-based core-shell catalyst prepared by the present invention has excellent synergistic oxidation performance for elemental mercury and escaped ammonia. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The three catalysts in anhydrous environment react with NH3 / Hg 0 Comparison chart of oxidation performance.

[0023] Figure 2 The results of the three catalysts on NH3 / Hg in a water environment (8% H2O added to simulated flue gas) 0 Comparison chart of oxidation performance. DETAILED DESCRIPTION

[0024] Example 1

[0025] A method for preparing a copper-cerium-based core-shell catalyst comprises the following steps:

[0026] A. Put Cu(NO3)2·3H2O into 0.1mmol / L ethanol aqueous solution, stir magnetically for 2h, transfer the ethanol aqueous solution to a 60℃ water bath and stir magnetically for 10min, then add TiO2, the mass ratio of TiO2 to Cu element is 20:1, then stir magnetically for 30min, then add 1mol / L NaOH aqueous solution, stir magnetically for 30min, then add 4mol / L glucose aqueous solution, stir magnetically for 1h, the volume ratio of ethanol aqueous solution, NaOH aqueous solution and glucose aqueous solution is 5:5:1.

[0027] B. Filter the solution to obtain a yellow precipitate, wash the precipitate with deionized water and anhydrous ethanol three to four times respectively, and then vacuum dry it at 50°C for 24 hours to obtain a Cu2O-TiO2 sample.

[0028] C. Place the Cu2O-TiO2 sample in a vacuum reaction chamber and draw the vacuum degree to less than 1×10 -3 Torr, the Cu2O-TiO2 sample was heated to 850℃, and then argon mixed with methyl manganocene was introduced, the content of methyl manganocene was 15mg / L, the flow rate of argon was 25sccm, the introduction of argon was stopped after 10min, the temperature was lowered to 600℃, maintained for 30min, then lowered to room temperature, the vacuum was broken, and the doping treatment was completed.

[0029] D. First, heat the doped Cu2O-TiO2 sample to 980℃, keep it for 5h, then cool it down to 350℃ at a rate of 30℃ / h, keep it for 24h, and then cool it down to room temperature at a rate of 80℃ / h to complete the annealing treatment.

[0030] E. Add the annealed Cu2O-TiO2 sample to an ethanol-water solution with a concentration of 0.1 mmol / L, and then add an NaCl aqueous solution with a concentration of 0.855 mol / L and an (NH4)2Ce(NO3)6 ethanol solution with a concentration of 0.1 mmol / L in sequence, and then magnetically stir for 30 minutes. Then transfer the mixed solution to a 40°C water bath heating environment and magnetically stir for 1 hour; the volume ratio of the ethanol-water solution, the NaCl aqueous solution and the (NH4)2Ce(NO3)6 ethanol solution is 20:2:5.

[0031] F. The solution obtained in step E is centrifuged, the precipitate is washed with ethanol several times, and dried under vacuum, and finally the dried product is calcined at a temperature of 400° C. for 1 h to obtain a copper-cerium-based core-shell catalyst.

[0032] Comparative Example 1

[0033] A method for preparing a copper-cerium-based core-shell catalyst comprises the following steps:

[0034] A. Put Cu(NO3)2·3H2O into 0.1mmol / L ethanol aqueous solution, stir magnetically for 2h, transfer the ethanol aqueous solution to a 60℃ water bath and stir magnetically for 10min, then add TiO2, the mass ratio of TiO2 to Cu element is 20:1, then stir magnetically for 30min, then add 1mol / L NaOH aqueous solution, stir magnetically for 30min, then add 4mol / L glucose aqueous solution, stir magnetically for 1h, the volume ratio of ethanol aqueous solution, NaOH aqueous solution and glucose aqueous solution is 5:5:1.

[0035] B. Filter the solution to obtain a yellow precipitate, wash the precipitate with deionized water and anhydrous ethanol three to four times respectively, and then vacuum dry it at 50°C for 24 hours to obtain a Cu2O-TiO2 sample.

[0036] C. Add the Cu2O-TiO2 sample to an ethanol-water solution with a concentration of 0.1mmol / L, and then add an NaCl aqueous solution with a concentration of 0.855mol / L and an (NH4)2Ce(NO3)6 ethanol solution with a concentration of 0.1mmol / L in sequence, and then stir magnetically for 30 minutes. Then transfer the mixed solution to a 40°C water bath heating environment and stir magnetically for 1 hour. The volume ratio of the ethanol-water solution, the NaCl aqueous solution and the (NH4)2Ce(NO3)6 ethanol solution is 20:2:5.

[0037] D. The solution obtained in step C is centrifuged, the precipitate is washed with ethanol several times, and dried under vacuum, and finally the dried product is calcined at a temperature of 400° C. for 1 h to obtain a copper-cerium-based core-shell catalyst.

[0038] Comparative Example 2

[0039] A method for preparing a copper-cerium-based core-shell catalyst comprises the following steps:

[0040] A. Put Cu(NO3)2·3H2O into 0.1mmol / L ethanol aqueous solution, stir magnetically for 2h, transfer the ethanol aqueous solution to a 60℃ water bath and stir magnetically for 10min, then add TiO2, the mass ratio of TiO2 to Cu element is 20:1, then stir magnetically for 30min, then add 1mol / L NaOH aqueous solution, stir magnetically for 30min, then add 4mol / L glucose aqueous solution, stir magnetically for 1h, the volume ratio of ethanol aqueous solution, NaOH aqueous solution and glucose aqueous solution is 5:5:1.

[0041] B. Filter the solution to obtain a yellow precipitate, wash the precipitate with deionized water and anhydrous ethanol three to four times respectively, and then vacuum dry it at 50°C for 24 hours to obtain a Cu2O-TiO2 sample.

[0042] C. Place the Cu2O-TiO2 sample in a vacuum reaction chamber and draw the vacuum degree to less than 1×10 -3 Torr, the Cu2O-TiO2 sample was heated to 850℃, and then argon mixed with methyl manganocene was introduced, the content of methyl manganocene was 15mg / L, the flow rate of argon was 25sccm, the introduction of argon was stopped after 10min, the temperature was lowered to 600℃, maintained for 30min, then lowered to room temperature, the vacuum was broken, and the doping treatment was completed.

[0043] D. Add the doped Cu2O-TiO2 sample to an ethanol-water solution with a concentration of 0.1 mmol / L, and then add an NaCl aqueous solution with a concentration of 0.855 mol / L and an (NH4)2Ce(NO3)6 ethanol solution with a concentration of 0.1 mmol / L in sequence, and then stir magnetically for 30 minutes. Then transfer the mixed solution to a 40°C water bath heating environment and stir magnetically for 1 hour. The volume ratio of the ethanol-water solution, the NaCl aqueous solution and the (NH4)2Ce(NO3)6 ethanol solution is 20:2:5.

[0044] E. The solution obtained in step D is centrifuged, the precipitate is washed with ethanol several times, and dried under vacuum, and finally the dried product is calcined at a temperature of 400° C. for 1 h to obtain a copper-cerium-based core-shell catalyst.

[0045] The catalysts prepared in the embodiment and the two comparative examples were subjected to NH3 / Hg 0 Oxidation performance comparison test, the results refer to Figure 1-2 From the test results, it can be seen that the copper-cerium-based core-shell catalyst prepared in the embodiment of the present invention has excellent synergistic oxidation performance for elemental mercury and escaped ammonia.

[0046] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a copper-cerium-based core-shell catalyst, characterized in that The following steps are involved: A. Put Cu(NO3)2·3H2O into ethanol aqueous solution, perform the first magnetic stirring, transfer the ethanol aqueous solution to a water bath heating environment, perform the second magnetic stirring, then add TiO2, perform the third magnetic stirring, then add NaOH aqueous solution, perform the fourth magnetic stirring, then add glucose aqueous solution, perform the fifth magnetic stirring; B. Filter the solution to obtain a yellow precipitate, wash the precipitate with deionized water and anhydrous ethanol respectively, and then vacuum dry to obtain a Cu2O-TiO2 sample; C. Place the Cu2O-TiO2 sample in a vacuum reaction chamber, heat the Cu2O-TiO2 sample after evacuation, and then introduce argon gas mixed with methyl manganocene for doping treatment; D. Annealing the Cu2O-TiO2 sample after doping; E. Add the annealed Cu2O-TiO2 sample to an ethanol aqueous solution, then add an NaCl aqueous solution and a (NH4)2Ce(NO3)6 ethanol solution in sequence, and then perform the sixth magnetic stirring, and then transfer the mixed solution to a water bath heating environment and perform the seventh magnetic stirring; F. The solution obtained in step E is centrifuged, the precipitate is washed with ethanol for several times, and dried under vacuum, and finally the dried product is calcined to obtain a copper-cerium-based core-shell catalyst.

2. The method for preparing the copper-cerium-based core-shell catalyst according to claim 1, characterized in that: In step A, the concentration of the ethanol aqueous solution is 0.1mmol / L, the first magnetic stirring time is 2h, the water bath heating temperature is 60°C, the second magnetic stirring time is 10min, the mass ratio of TiO2 to Cu element is 20:1, the third magnetic stirring time is 30min, the concentration of the NaOH aqueous solution is 1mol / L, the fourth magnetic stirring time is 30min, the concentration of the glucose aqueous solution is 4mol / L, the fifth magnetic stirring time is 1h, and the volume ratio of the ethanol aqueous solution, the NaOH aqueous solution and the glucose aqueous solution is 5:5:

1.

3. The method for preparing the copper-cerium-based core-shell catalyst according to claim 2, characterized in that: In step B, the precipitate is washed three to four times with deionized water and anhydrous ethanol respectively, and then vacuum dried at 50° C. for 24 h.

4. The method for preparing the copper-cerium-based core-shell catalyst according to claim 3, characterized in that: In step C, the vacuum degree is drawn to less than 1×10 -3 Torr, the Cu2O-TiO2 sample was heated to 850℃, the content of methyl manganocene was 15mg / L, the flow rate of argon was 25sccm, the introduction of argon was stopped after 10min, the temperature was lowered to 600℃, maintained for 30min, then lowered to room temperature, the vacuum was broken, and the doping treatment was completed.

5. The method for preparing the copper-cerium-based core-shell catalyst according to claim 4, characterized in that: In step D, the doped Cu2O-TiO2 sample is first heated to 980°C and maintained for 5 hours, then cooled to 350°C at a rate of 30°C / h and maintained for 24 hours, and then cooled to room temperature at a rate of 80°C / h to complete the annealing treatment.

6. The method for preparing the copper-cerium-based core-shell catalyst according to claim 5, characterized in that: In step E, the concentration of the ethanol aqueous solution is 0.1 mmol / L, the concentration of the NaCl aqueous solution is 0.855 mol / L, the concentration of (NH4)2Ce(NO3)6 in the (NH4)2Ce(NO3)6 ethanol solution is 0.1 mmol / L, the time of the sixth magnetic stirring is 30 min, the water bath heating environment temperature is 40°C, and the time of the seventh magnetic stirring is 1 h; the volume ratio of the ethanol aqueous solution, the NaCl aqueous solution and the (NH4)2Ce(NO3)6 ethanol solution is 20:2:

5.

7. The method for preparing the copper-cerium-based core-shell catalyst according to claim 6, characterized in that: In step F, the calcination temperature is 400° C. and the calcination time is 1 h.

8. A copper-cerium-based core-shell catalyst, characterized in that: The catalyst is prepared by the method for preparing the copper-cerium-based core-shell catalyst according to any one of claims 1 to 7.

Citation Information

Cited By

  • Preparation method of additive and application of additive in polycarbonate engineering plastics

    CN119613698A

  • Preparation method of an additive and application thereof in polycarbonate engineering plastics

    CN119613698B